ANALISIS KEBUTUHAN MODAL KERJA PADA RUMAH MAKAN BINTANG LIMA DI SAMARINDA - Yundi Permadi Hakim; Santi Mulyani (Universitas Muhammadiyah Kalimantan Timur, 2017)
Working Capital Needs Analysis at Star Restaurant in Samarinda. In its operational activity, sometimes the excess or insufficiency of working capital hence the usage of the fund less effective and efficient until now the owner of Bintang Restaurant in Samarinda not yet know the actual condition and have not yet analyzed the use of working capital requirement whether need the addition of working capital or not, more in the future. The formulation of the problem in this research is: